(untitled) - Holm, I.; Fosdahl, M. A.; Friis, A.; Risberg, M. A.; Myklebust, G.; Steen, H. (Clinical Journal of Sport Medicine, 2004)
Abstract: Objective: Introduction of a neuromuscular training program will increase muscle strength, balance, and proprioception in elite female handball players. Design: Prospective intervention study. Participants: Thirty-five female team handball players from 2 teams in the elite division participated. Their mean age was 23 (+/-2.5) years, and their mean weight was 69.2 (+/-7.3) kg. They had played handball for 14.9 (+/-3.2) years, 4.7 (+/-2.8) years at the top level. The total number of training hours per week was 10 to 11. Intervention: Based on earlier studies and knowledge about common risk situations in team handball, an anterior cruciate ligament (ACL) injury prevention program with 3 different sets of exercises was developed, each set with a 5-step progression from simple to more challenging exercises. The teams were instructed to use the program a minimum of 3 times a week during a training period of 5 to 7 weeks, and then once a week during the season. The duration of each training session was approximately 15 minutes. Main outcome measures: Balance (KAT 2000), proprioception (threshold to detection of passive motion), muscle strength (Cybex 6000), and 3 functional knee tests. The players were tested pretraining (test 1) and 8 weeks (test 2) and 12 months (test 3) after the training started. Results: There was a significant improvement in dynamic balance between test 1 and test 2, with a balance index (BI) of 924 (+/-225) and 778 (+/-174), respectively (P = 0.01). The effect on dynamic balance was maintained 1 year after training (BI, 730 +/- 156). For static balance, no statistically significant changes were found. For the other variables measured, there were no statistical differences during the study period. Conclusion: The ACL injury prevention training program improved dynamic balance in an elite team handball players.